PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA AKADEMIK PADA PENDIDIKAN ANAK USIA DINI TERATAI PUTIH BERBASIS WEBSITE - Fikastiana Cahya (2021)
The use of information technology, especially in the world of education, is very important today, because almost all educational institutions use technology to support the performance of employees and teachers. One of the uses of technology currently needed in education is processing student academic data. Academic data processing at educational institutions, especially in PAUD Teratai Putih, needs to be considered because currently in implementing student data processing is still done by hand or manually. In the process, manual data collection is considered quite slow because it requires very high accuracy to reduce errors in the data collection process and to maintain the accuracy of the data. In processing student data, student attendance, and student scores at PAUD Teratai Putih, it is necessary to develop an information system to process data and streamline time. Data recording and reports on ledgers often experience loss, because each year the data continues to increase and is difficult to find and requires long student data. So, the purpose of this study is to design a website-based academic data processing information system at PAUD Teratai Putih which will facilitate data processing. In developing this system using the prototype method stages and programming languages using MySQL and PHP.